A comparative study based on localized surface plasmon resonance optical characteristics of green synthesized nanoparticles towards spectrophotometric determination of cupric ions. Issue 1 (31st December 2022) - Shahzadi, Tayyaba; Iqbal, Shazia; Riaz, Tauheeda; Zaib, Maria
ABSTRACT: In this study, green synthesis of monometallic (Ag) and bimetallic (Ag-Ni) nanoparticles is carried out. UV-Visible spectra illustrated peaks at 463 and 429 nm for monometallic and bimetallic nanoparticles. FTIR spectra analysis revealed the presence of different functional groups. SEM and EDX elaborated on the morphology and indicate the presence of respective elemental peaks. XRD data calculations predicted the size of monometallic and bimetallic to be 42 and 25 nm. In the end, the biosynthesized nanoparticles are used as a spectrophotometric probe for the determination of cupric ions. Different parameters are studied and optimized on a standard aqueous solution. Monometallic nanoparticles showed an optimum response in a slightly alkaline medium within 12.5 min of contact time for 8 μM analyte concentration. While bimetallic nanoparticles attained this target in a shorter contact time with a higher concentration value. Then these optimized conditions are utilized for the determination of cupric ions in real water samples. GRAPHICAL ABSTRACT: UF0001